(untitled) (Revista de Ciências Agroveterinárias, 2006)
The residues produced by paper recycling industries, commonly known as paper mill sludge, present some constituents that can correct soil acidity and act as nutrients source, mainly calcium. However, these residues may also have heavy metals, which can cause environmental impact. The aim of this work was to evaluate the effect of different rates of lime and two kinds of recycling paper industry residues on the growth and mineral composition (nutrients and heavy metals) of lettuce tissue. The effect of lime and two kinds of recycling paper industry residues, applied in five doses, on lettuce dry mass and lettuce tissue levels of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, cupper, zinc, iron, manganese, sodium, bore, cadmium, chromo, nickel, lead and mercury were evaluated. The application of lime and two kinds of recycling paper industry residues increased lettuce dry mass and did not affect lettuce tissue levels of nutrients and heavy metals concentration.